2018
DOI: 10.1002/jmv.25036
|View full text |Cite
|
Sign up to set email alerts
|

Dobrava hantavirus variants found in Apodemus flavicollis mice in Kırklareli Province, Turkey

Abstract: Hantaviruses infect humans via inhalation of viral particles within secretions of infected rodents or rarely through direct contact with infected rodents. Determining the prevalence of hantavirus infections among rodent populations is of vital importance to obtain information on hantavirus-related cases and to predict possible outbreaks. We hypothesized that DOBV strains circulating in the Thrace Region in Turkey would be related to other Balkan DOBV strains. In this study, hantavirus infections in the rodent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…DOBV RNA has been identified in A. flavicollis and A. uralensis in the outbreak region (Oktem et al, ). Recently, DOBV was identified in A. flavicollis in the Thrace Region (near Bulgaria), and TULV RNA was identified in Microtus obscurus in the East Anatolian Region of the country (Polat et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOBV RNA has been identified in A. flavicollis and A. uralensis in the outbreak region (Oktem et al, ). Recently, DOBV was identified in A. flavicollis in the Thrace Region (near Bulgaria), and TULV RNA was identified in Microtus obscurus in the East Anatolian Region of the country (Polat et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DOBV was identified in A. flavicollis in the Thrace Region (near Bulgaria), and TULV RNA was identified in Microtus obscurus in the East Anatolian Region of the country (Polat et al, 2019(Polat et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…After these outbreaks and diagnoses, a field study was performed by collecting Apodemus flavicollis mice from the Kirklareli province by our team, and the circulation of DOBV was confirmed in this species of mice both serologically and molecularly [11]. Studies done to date have shown that DOBV causes severe form of HFRS in humans, and the mortality rate is higher in DOBV infections than the other HFRS causing orthohantaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reservoir host Apodemus flavicollis is distributed in both European side and Anatolia (Asian side of Turkey), and it shows different genetic properties on these sides [26][27]. Therefore, orthohantaviruses that exist in this region, might have genetic properties of viruses from both of these continents [11,25]. Thus, there is great importance to obtain whole genome sequences of DOBV from this region as these might help us to understand the genetic relation between orthohantaviruses from both Asia and Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation